2023
DOI: 10.1128/jvi.01672-22
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Trial of anle138b in Mouse Models of Genetic Prion Disease

Abstract: There is an urgent need to develop drugs for prion disease, a currently untreatable neurodegenerative disease. In this effort, there is a debate over which animal models can best support a drug development program.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
3
4
0
Order By: Relevance
“…We observed that PSCMA potently inhibited D177N PrP Sc propagation in recombinant sPMCA reactions, but PSCMA had no therapeutic effect in vivo . Our results also suggest that the novel knock-in models of FFI and fCJD that we used for these studies may be generally advantageous for pre-clinical in vivo testing because they have physiological PrP expression levels and shortened lifespans, thereby providing an objective and quantifiable endpoint for evaluating therapeutic efficacy, as recently suggested by Vallabh and Minikel(25). Finally, our results suggest that less easily administered therapies which lower PrP levels (such as anti-sense oligonucleotides delivered by lumbar puncture) may ultimately be required to escape the ability of both wild-type and mutant prions to undergo strain-adaptation leading to anti-prion drug failure(32, 44, 45).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We observed that PSCMA potently inhibited D177N PrP Sc propagation in recombinant sPMCA reactions, but PSCMA had no therapeutic effect in vivo . Our results also suggest that the novel knock-in models of FFI and fCJD that we used for these studies may be generally advantageous for pre-clinical in vivo testing because they have physiological PrP expression levels and shortened lifespans, thereby providing an objective and quantifiable endpoint for evaluating therapeutic efficacy, as recently suggested by Vallabh and Minikel(25). Finally, our results suggest that less easily administered therapies which lower PrP levels (such as anti-sense oligonucleotides delivered by lumbar puncture) may ultimately be required to escape the ability of both wild-type and mutant prions to undergo strain-adaptation leading to anti-prion drug failure(32, 44, 45).…”
Section: Discussionsupporting
confidence: 66%
“…Although treatment of inherited prion diseases appears to be a tractable goal, there have been no drugs specifically developed to target mutant prions. Recently, Vallabh et al accurately noted that a longstanding barrier to developing and testing such drugs pre-clinically has been the lack of animal models of inherited prion disease that exhibit shortened lifespans without transgene overexpression (25). Here, we evaluate several drug regimens that can either inhibit wild-type PrP Sc accumulation and prolong incubation time in scrapie-infected animals or inhibit mutant PrP Sc propagation in sPMCA reactions for their ability to treat new knock-in mouse models of FFI and fCJD with shortened lifespans.…”
mentioning
confidence: 99%
“…We observed that PSCMA potently inhibited D178N PrP Sc propagation in recombinant sPMCA reactions, but PSCMA had no therapeutic effect in vivo . Our results also suggest that the novel knock-in models of FFI and fCJD that we used for these studies may be generally advantageous for pre-clinical in vivo testing because they have physiological PrP expression levels and shortened lifespans, thereby providing an objective and quantifiable endpoint for evaluating therapeutic efficacy, as recently suggested by Vallabh and Minikel [ 25 ]. Finally, our results suggest that less easily administered therapies which lower PrP levels (such as anti-sense oligonucleotides delivered by lumbar puncture) may ultimately be required to escape the ability of both wild-type and mutant prions to undergo strain-adaptation leading to anti-prion drug failure [ 31 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 55%
“…Theoretically, using animal models with lower expression levels and fewer plaques should improve our ability to detect a therapeutic effect and therefore increase our confidence about the negative results observed in this study. A more recent study testing Anle138b in alternative knock-in mouse models of FFI and fCJD expressing mutant mouse PrP molecules rather than bank vole PrP molecules was limited by the relatively normal lifespan of those mutant mice [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the compound showed effectiveness in several animal models, it failed to fully restore neural function in an acute neurotoxin-based MSA model [ 270 ]; therefore, combination with another compound, somewhat more specific to oxidative-stress-related apoptosis, should be considered. Also, in mouse models of genetic prion disease, anle138b appeared to be less effective as compared to sporadic model of this disorder [ 271 ]. The molecule has already completed two phase I trials in PD patients and healthy volunteers (NCT04685265; NCT04208152).…”
Section: Drugs Targeting α-Synucleinmentioning
confidence: 99%